Rancang Bangun Cetakan Alat Press Pelepah Pinang Menjadi Wadah Makanan Ramah Lingkungan untuk UMKM - Araliz, Maheka Restu; Adril, Elvis; Budiman, Daddy; Mutia, Mutia (Politeknik Negeri Padang, 2025)
The issue of plastic waste has become a global concern that urgently needs to be addressed. On the other hand, agricultural waste also poses its own challenges. Indonesia is an agrarian country where the agricultural sector plays a significant and vital role in the national economy. One of the major agricultural products in Indonesia, particularly in West Sumatra, is areca nut (betel nut). The areca palm sheath is largely underutilized by farmers, often left unused or burned, which in turn leads to another issue—air pollution. The transformation of organic solid waste into eco-friendly products is still rarely implemented. This study aims to design, assemble, and test a simple press mold to process areca palm sheaths into environmentally friendly food containers. The results show that the mold was successfully designed with dimensions of 140 mm x 140 mm x 20 mm, using ST 42 material. Mold testing with temperature variations (100°C, 150°C, and 175°C) and durations (1 minute, 2 minutes, and 5 minutes) indicated that a temperature of 150°C produced the best results in terms of color and shape accuracy. This innovation is expected to support small and medium enterprises (SMEs) in reducing plastic waste and utilizing areca palm sheath waste.